2013
DOI: 10.1128/aem.02761-12
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic, Metabolic, and Taxonomic Diversities Shape Mediterranean Fruit Fly Microbiotas during Ontogeny

Abstract: The Mediterranean fruit fly (medfly) (Ceratitis capitata) lays eggs in fruits, where larvae subsequently develop, causing largescale agricultural damage. Within its digestive tract, the fly supports an extended bacterial community that is composed of multiple strains of a variety of enterobacterial species. Most of these bacteria appear to be functionally redundant, with most strains sustaining diazotrophy and/or pectinolysis. At least some of these bacteria were shown to be vertically inherited, but colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 69 publications
12
103
0
2
Order By: Relevance
“…Similar findings of a predominantly vertical transmission with a low rate of horizontal transmission (that is, mixed transmission mode) in a range of other insects challenge the traditional view of a strict vertical transmission of most insect mutualists and instead highlight the importance of mixed transmission modes across a wide range of host taxa (Ebert, 2013). Examples for this mixed transmission mode include burying beetles (Kaltenpoth and Steiger 2014), fruit flies (Aharon et al, 2013), beewolves , termites (Schauer et al, 2012) and bumblebees (Koch and Schmid-Hempel, 2011).…”
Section: Mixed Transmission Mode and Partner Specificitymentioning
confidence: 61%
“…Similar findings of a predominantly vertical transmission with a low rate of horizontal transmission (that is, mixed transmission mode) in a range of other insects challenge the traditional view of a strict vertical transmission of most insect mutualists and instead highlight the importance of mixed transmission modes across a wide range of host taxa (Ebert, 2013). Examples for this mixed transmission mode include burying beetles (Kaltenpoth and Steiger 2014), fruit flies (Aharon et al, 2013), beewolves , termites (Schauer et al, 2012) and bumblebees (Koch and Schmid-Hempel, 2011).…”
Section: Mixed Transmission Mode and Partner Specificitymentioning
confidence: 61%
“…In this study we found that B. dorsalis appears to have a relatively higher diversity of bacterial symbionts when compared to Ceratitis capitata and Drosophila melanogaster . High throughput analysis of bacteria population of the C. capitata revealed only 5–23 OTUs and 7–13 OTU of bacteria symbionts to be associated with the adult fly and larva respectively at 97% sequence identity21. Similarly 454 pyrosequencing of gut bacteria community associated with D. melanogaster yielded a total of 122 OTU at 97% sequencing identity22.…”
Section: Discussionmentioning
confidence: 99%
“…Aharon et al . () considered this finding in order to explain the increasing polyphyly of the Enterobacteriaceae during ontogeny in C. capitata . It could be hypothesized that the acquisition of endemic bacteria during the initial phases of invasion of a new region could lead to inflammatory disorders in the D. suzukii gut and generate transient enterobacterial blooms which, similarly, favor the reassortment of genetic material and confer habitat‐adapted fitness benefits to bacteria.…”
Section: Discussionmentioning
confidence: 99%